Excessive Force in the New York City Jails: Litigation and Its Lessons - John Boston (Washington University Journal of Law & Policy, 2006)
The New York City Legal Aid Society, through its Prisoners’ Rights Project (PRP), has fought since PRP’s founding in 1971 to protect the human rights of prisoners. In particular, we have wrestled with the problem of excessive force by New York City jail staff through individual and class action litigation and through investigations and demands for administrative redress on behalf of injured prisoners. Our focus has been on reforming the systems that operate to control force in correctional settings including written policy, training, investigations, discipline, and supervision of staff. The single most important lesson we have taken from twenty years of litigation is that the controlling force in jails and prisons is a function of correctional leadership. When supervisory staff makes a visible, demonstrable commitment to curb misuse of force and hold staff accountable, inmates will not get brutalized. When correction supervisors turn a blind eye toward misconduct by condoning excessive force, overlooking false reports, and imposing inadequate punishment when brutality is identified, they send a signal to line staff that they can control troublesome, disruptive or defiant prisoners simply by beating them.
Keywords: Prisoners& #x27; litigation; Correctional personnel; Prisoners – Civil rights; Prison violence; Prisoners; Jails; Force (Law); Prisoner abuse; New York; United States